2020
DOI: 10.3389/fphys.2020.574339
|View full text |Cite
|
Sign up to set email alerts
|

The Probable, Possible, and Novel Functions of ERp29

Abstract: The luminal endoplasmic reticulum (ER) protein of 29 kDa (ERp29) is a ubiquitously expressed cellular agent with multiple critical roles. ERp29 regulates the biosynthesis and trafficking of several transmembrane and secretory proteins, including the cystic fibrosis transmembrane conductance regulator (CFTR), the epithelial sodium channel (ENaC), thyroglobulin, connexin 43 hemichannels, and proinsulin. ERp29 is hypothesized to promote ER to cis-Golgi cargo protein transport via COP II machinery through its inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 133 publications
0
8
0
1
Order By: Relevance
“…Since ZHX2 is also associated with cortical neuronogenesis [ 42 ], it may be associated with the progression to dementia. ERP29 gene encodes a 29 kDa endoplasmic reticulum protein (ERp29), which is ubiquitously expressed in cells and regulates protein transport between the endoplasmic reticulum and Golgi apparatus [ 44 ]. ERp29 is involved in protein misfolding and mistrafficking [ 44 , 45 ], which are potent pathogenic features of PD and Alzheimer’s disease [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since ZHX2 is also associated with cortical neuronogenesis [ 42 ], it may be associated with the progression to dementia. ERP29 gene encodes a 29 kDa endoplasmic reticulum protein (ERp29), which is ubiquitously expressed in cells and regulates protein transport between the endoplasmic reticulum and Golgi apparatus [ 44 ]. ERp29 is involved in protein misfolding and mistrafficking [ 44 , 45 ], which are potent pathogenic features of PD and Alzheimer’s disease [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…ERP29 gene encodes a 29 kDa endoplasmic reticulum protein (ERp29), which is ubiquitously expressed in cells and regulates protein transport between the endoplasmic reticulum and Golgi apparatus [ 44 ]. ERp29 is involved in protein misfolding and mistrafficking [ 44 , 45 ], which are potent pathogenic features of PD and Alzheimer’s disease [ 46 ]. Given that endoplasmic reticulum stress is related to Lewy body dementia [ 47 ], it is possible that ERp29 mutation also induces cortical neuronal damage and is linked to the progression of dementia in patients with PD.…”
Section: Discussionmentioning
confidence: 99%
“…Endoplasmic reticulum (ER) protein 29 (ERp29) is highly expressed throughout mammalian tissues. It predominantly acts as an ER to Golgi escort/chaperone proteins [ 103 , 104 , 105 , 106 ]. Cancer research revealed additional properties of ERp29, including cell growth arrest and involvement in MET.…”
Section: The Metastatic Cells Journey To the Brainmentioning
confidence: 99%
“…Günümüze kadar memeli hücrelerinde UPR yolağının uyarılmasından, ER lümenindeki katlanmamış proteinler tarafından aktive edilen, ER zarına yerleşik üç sinyal molekülü keşfedilmiştir: İnositol gerektiren kinaz 1 (IRE1), aktive edici transkripsiyon faktörü 6 (ATF6) ve protein kinaz RNA benzeri ER kinaz (PERK)(Şekil 3) 28,29 . Bu üç sinyal molekülünün odakta olduğu UPR yolaklarıyla katlanmamış ya da hatalı katlanan proteinlere karşı hücre homeostazı düzenlenmektedir.…”
Section: Granüllü Endoplazmik Retikulumda Proteinlerin Kalite Kontrol...unclassified